Analysis of the Real-Time Phases of Adaptation Through the Lens of an Emergent Risk: Sargassum Adaptation Policy Analysis in the Caribbean - Sien van der Plank; Janice Cumberbatch; Bethia Thomas; Jack Corbett; Emma L. Tompkins (Phycology)
Since 2011, countries across the tropical Atlantic have experienced severe influxes of the seaweed species Sargassum natans and Sargassum fluitans (henceforth, “sargassum”), with nearshore and onshore ecological, economic and social impacts locally and regionally. Not all affected countries have had the same response to this emergent environmental challenge. Here, we explore the first ten years of policies produced in response to sargassum influx risk across islands in the Wider Caribbean Region, considering the variation in form, content and aim of sargassum adaptation policies. This assessment of the variation in Caribbean adaptation policies allows lessons to be identified for rapid adaptation to emergent environmental challenges. We find that several countries have no national policy for sargassum adaptation, and many subnational island jurisdictions have no island-specific policies. Whilst there is increasing anecdotal evidence of private and local adaptations taking place to address sargassum influx events, there remains significant scope for government leadership and resource support in adapting to this emergent threat. The lesson is that private adaptations to emergent threats may be quicker to develop and execute than policy adaptation, but longer-term, larger-scale adaptations depend on evidence-based, widely supported government policies with clear avenues of funding.